The answer is 24. To get to each term, we can see that the value is decreasing by 7. So 31 - 7 = 24
Answer:
aww you had my question opennnn
Step-by-step explanation:
Answer:
b
Step-by-step explanation:
Answer:
<h2><u><em>
5</em></u></h2>
Step-by-step explanation:
X * 3^2 +2 = 47
X * 9 + 2 = 47
9X = 47 - 2
9x = 45
x = 45 : 9
X = 5
Answer:
<u>C) −2x − 2y + 17</u>
Step-by-step explanation (PEMDAS):
First, we do <u>3 (y + 5)</u> because of the parenthesis:
6x − 5y + 2 − 8x + 3y + 15
Since there are no exponents, multiplication ,or division, we will add and subtract. But we have to make sure we <u>combine like terms</u>. X with X's, Y with Y's and constants with constants. And ALWAYS go from left to right
6x − 5y + 2 − 8x + 3y + 15
<u>−2x</u> − 5y + 2 + 3y + 15
−2x <u>− 2y</u> + 2 + 15
<em>−2x − 2y</em><em> </em><em>+ </em><em><u>17</u></em><em>.</em>